2012
DOI: 10.1177/0954405412467141
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic analysis on fabricated mineral cast lathe bed

Abstract: Vibrations transmitted into the machine tool structure made of cast iron cause chattering and develop positional errors between the components during machining operations, causing dimensional inaccuracy and poor surface finish for the products manufactured from them. As an alternate material for cast iron, mineral cast epoxy granite structures are found to exhibit good mechanical properties such as high stiffness and damping ratio at a lesser weight. This study attempts to fabricate an epoxy granite lathe bed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…Figure 5 shows the decay graphs of the amplitude by time: The damping coefficient values by the Logarithmic Decrement Method [29] calculated for the three materials are shown in Table 1: The produced synthetic granite composite presented excellent average damping coefficient, 5.5 times greater than aluminum 6061 and 6.2 times greater than gray cast iron, two materials usually used in machine structures and precision equipment. These measured values of aluminum damping coefficient and cast iron [30][31][32], as well the damping coefficient measured by the granite composition [8,33]. These results show the advantage of synthetic granite for the vibrations absorption in mechanical structures, compared to metals traditionally used for this purpose, inciting its application in structures of machine tools and measurement machines.…”
Section: Resultssupporting
confidence: 54%
“…Figure 5 shows the decay graphs of the amplitude by time: The damping coefficient values by the Logarithmic Decrement Method [29] calculated for the three materials are shown in Table 1: The produced synthetic granite composite presented excellent average damping coefficient, 5.5 times greater than aluminum 6061 and 6.2 times greater than gray cast iron, two materials usually used in machine structures and precision equipment. These measured values of aluminum damping coefficient and cast iron [30][31][32], as well the damping coefficient measured by the granite composition [8,33]. These results show the advantage of synthetic granite for the vibrations absorption in mechanical structures, compared to metals traditionally used for this purpose, inciting its application in structures of machine tools and measurement machines.…”
Section: Resultssupporting
confidence: 54%
“…It was observed that the damping ratio of epoxy granite bed is improved by 2.2 times greater than cast iron bed. The weight of the epoxy granite lathe bed in comparison with cast iron bed was reduced by 38.64 % for same stiffness [7].…”
Section: Structure Redesignmentioning
confidence: 92%
“…3 Polymer concrete with viscoelastic matrix (basalt and quartzite with 10% epoxy resin) was observed to provide noteworthy increase in damping (up to 160 Hz) when compared to cast iron material. 4 Selvakumar et al 5 investigated on polymer concrete (PC) lathe bed and it was found that PC lathe bed have 2.2 times higher damping and 38.64% reduction in weight when compared to the cast iron lathe bed. Mahendrakumar et al 6 developed a micro-lathe bed using Himalayan nettle polyester composite as an alternative material to investigate its static and dynamic characteristics.…”
Section: Introductionmentioning
confidence: 99%